2022
DOI: 10.1051/sicotj/2022009
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of double level osteotomy for osteoarthritic knees with severe varus deformity. A systematic review

Abstract: Background: When correcting severe genu varus deformity, knee surgeons must choose between performing a single or double-level osteotomy. This systematic review aims to provide this equipoise with some clarity. Patients and methods: We conducted this study following the Preferred Reporting Items for Systematic Reviews and Meta-analyses Statement (PRISMA) and the Cochrane Handbook for systematic reviews and meta-analysis. Studies evaluating the effect of the double level osteotomy (DLO) or those comparing it to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Double‐level knee osteotomy is another attractive option that can be employed to address unicompartmental varus knee OA to achieve physiological alignment parameters in cases with severe deformities [9, 28]. Nevertheless, Nejima et al [29] reported an increased preoperative JLCA to be a risk factor for increased postoperative medial proximal tibial angle (MPTA > 95°) in 41% of the cases undergoing planning for double‐level knee osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Double‐level knee osteotomy is another attractive option that can be employed to address unicompartmental varus knee OA to achieve physiological alignment parameters in cases with severe deformities [9, 28]. Nevertheless, Nejima et al [29] reported an increased preoperative JLCA to be a risk factor for increased postoperative medial proximal tibial angle (MPTA > 95°) in 41% of the cases undergoing planning for double‐level knee osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, medial closed wedge distal femoral osteotomy (DFO) 8 , 9 for valgus knees and lateral closed wedge DFO combined with medial OWHTO or lateral CWHTO; i.e. , double-level osteotomy 10 , 11 , 12 for severe varus knees are also becoming more common since the launch of various around-knee osteotomy (AKO)-specific locking plates. As a result, coronal alignment correction for uni-compartmental knee osteoarthritis with a varus/valgus deformity is a well-established option.…”
Section: Introductionmentioning
confidence: 99%
“…There are concerns, however, that DLO remains a challenging procedure with no additional clinical benefit and an increased rate of complications. 6 …”
mentioning
confidence: 99%
“…There are concerns, however, that DLO remains a challenging procedure with no additional clinical benefit and an increased rate of complications. 6 The purpose of this study was to compare the clinical and radiological results between isolated OWHTO and DLO in patients with combined varus deformity and to analyze the rate of hinge fractures between these 2 groups. We hypothesized that DLO would improve clinical results without increasing the complication rate compared with OWHTO.…”
mentioning
confidence: 99%